2020
DOI: 10.1016/j.ijid.2020.06.105
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the probable outbreak size of novel coronavirus (COVID-19) in social gathering events and industrial activities

Abstract: Background: The reproduction number (R 0 ) is vital in epidemiology to estimate the number of infected people and trace close contacts. R 0 values vary depending on social activity and type of gathering events that induce infection transmissibility and its pathophysiology dependence. Objectives: In this study, we estimated the probable outbreak size of COVID-19 clusters mathematically using a simple model that can predict the number of COVID-19 cases as a function of time. Methods: We proposed a mathematical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…23 Interventions targeting increased physical distancing and limiting contact were introduced in some countries, including the closure of schools, places of worship, malls, and offices. 22 Our model suggests that specifically exempting religious gatherings from bans may increase the laCFR, consistent with the combination of findings that (1) religious gatherings across the globe were linked to COVID-19 superspreader events 24 and (2) older Americans (who are more likely to attend religious services than younger Americans 25 ) are at increased risk of death due to COVID-19.…”
Section: Discussionsupporting
confidence: 78%
“…23 Interventions targeting increased physical distancing and limiting contact were introduced in some countries, including the closure of schools, places of worship, malls, and offices. 22 Our model suggests that specifically exempting religious gatherings from bans may increase the laCFR, consistent with the combination of findings that (1) religious gatherings across the globe were linked to COVID-19 superspreader events 24 and (2) older Americans (who are more likely to attend religious services than younger Americans 25 ) are at increased risk of death due to COVID-19.…”
Section: Discussionsupporting
confidence: 78%
“…The literature reported that R 0 ranges between 2.3 and 6.5 [ 28 , 35 , 36 , 37 ] and a re-analysis of Chinese data provided an updated estimate of 5.7 (95% CI 3.8–8.9) [ 37 ]. Other published studies reported that, for social gathering events such as wedding parties in Jordan, the R 0 value was five [ 38 ].…”
Section: Figurementioning
confidence: 99%
“…A similar study conducted in Japan identified how, apart from healthcare facilities (where the largest number of infection clusters was identified), the largest number of virus outbreaks was identified in bars, restaurants, workplaces, gyms and public transport [67]. Different studies identified the connection between outbreaks of COVID-19 and venues with low ventilation rates or limited social distancing, such as meat and poultry facilities [68], trains [69], buses [70], cruise ships [71], choir rehearsal [72], bath centre [73], call centre [74], churches [75], fitness dance classes [76], mountain chalets [77], etc. Some actions involving the production of a significant amount of large droplets and small aerosols, such as singing, loud speaking, exercising, etc., were regarded as potentially responsible for these high rates of infection [67].…”
Section: Airborne Transmissionmentioning
confidence: 99%